Modal Kerja dan Pertumbuhan Laba: Peran Moderasi Leverage pada Perusahaan Farmasi di BEI Periode 2019–2024 - Okta Ulia Trisuciati; Boy Singgih Gitayuda (Jurnal Kajian Ilmu Manajemen (JKIM), 2026)
This study aims to analyze the importance of working capital management and leverage in enhancing profit growth in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The main focus of this research is to examine the effect of cash turnover, receivables turnover, and inventory turnover on profit growth, with leverage as a moderating variable. These variables were selected to reflect the effectiveness of working capital management that directly contributes to the company’s financial performance, while leverage represents the use of debt in supporting the company’s expansion and operations. This research employs a quantitative method with moderation regression analysis using secondary data from the companies’ annual financial reports. The results indicate that cash turnover and receivables turnover do not have a significant effect on profit growth. However, inventory turnover shows a significant effect. Furthermore, leverage is proven to moderate the relationship between cash turnover, receivables turnover, and inventory turnover on profit growth.